A history of medical libraries and medical librarianship from John Shaw Billings to the digital era - Kronenfeld, Michael R.; Kronenfeld, Jennie J. (Medical Library Association books, 2021)
This book covers the history of medical libraries and librarianship from the founding of the Medical Library Association in 1898 to today. The authors present the different stages in the evolution of health science librarianship and conclude with a discussion of the new, digital era of health science libraries.